Longitudinal reference range for umbilical cord cross‐sectional area in twin pregnancies at 18–32 weeks of gestation. (May 2015) - Fernandes, D. B.; Liao, A. W.; Brizot, M. L.; Francisco, R. P. V.; Zugaib, M.
Abstract Objectives The objectives of this study were to establish gestational age‐specific reference ranges for cross‐sectional area of the umbilical cord, and its components, in twin pregnancies and to compare them with previously reported singleton reference ranges. Methods This was a prospective longitudinal study involving uncomplicated dichorionic twin pregnancies. Sonographic measurements of the cross‐sectional area of the umbilical cord, umbilical vein and arteries and Wharton's jelly were obtained in a plane adjacent to the fetal abdomen, every 3 weeks, between 18 and 32 weeks of gestations. Multilevel regression analysis was used to determine gestational age‐specific reference ranges for each parameter, and these were plotted against singleton pregnancy references. Results Three hundred and thirty four ultrasound scans were performed in 44 twin pregnancies, between 18 and 32.9 weeks (mean: 3.8 ± 0.7 scans/pregnancy and mean interval between scans: 3.3 ± 0.9 weeks). All umbilical cord cross‐sectional areas (total, vein, artery and Wharton's jelly) showed a significant increase with gestational age. Compared with singleton pregnancy ranges, mean values were considerably lower in twin pregnancies and resemble the lower limits observed in singletons. Conclusion In twin pregnancies, cross‐sectional area of the umbilical cord, and its components, increases between 18 and 32 weeks, and mean values are substantially lower compared with singleton pregnancies. © 2015 John Wiley & Sons, Ltd.